RISING RATES OF CAESAREAN SECTION IN dr. ZAINOEL ABIDIN HOSPITAL BANDA ACEH SINCE THE PROMULGATION OF BPJS (PERIODJANUARY 1ST 2014-DECEMBER 31ST 2016) - Mohd. Andalas; Raudhatul Jannah; Siti Harisah; Ichsan Ichsan; Muhammad Haekal (Jurnal Kedokteran Syiah Kuala, 2018)
Abstrak. Seksio sesarea merupakan suatu proses melahirkan janin dengan membuat irisan pada dinding perut dan rahim ketika proses persalinan normal tidak memungkinkan karena berisiko bagi ibu dan janin. Angka kejadian seksio sesarea di dunia mengalami peningkatan setiap tahunnya terutama di negara berkembang. Terlihat peningkatan angka seksio sesarea di era BPJS yang mulai berlaku sejak 1 Januari 2014, terutama di RSUD dr. Zainoel Abidin yang merupakan rumah sakit rujukan tersier di Provinsi Aceh. Tujuan penelitian ini adalah untuk mengetahui profil persalinan seksio sesarea di RSUD dr. Zainoel Abidin Banda Aceh sejak berlakunya BPJS (periode 1 Januari 2014-31 Desember 2016). Penelitian ini bersifat deskriptif-observasional dengan desain retrospective study dan teknik total sampling.Pengambilan data dimulai dari bulan Maret-April 2017. Sebanyak 3656 data dikumpulkan dari data sekunder rekam medik. Hasil penelitian menunjukkan terdapat 1669 kasus persalinan pervaginam (45,65%) dan 1987 kasus seksio sesarea (54,35%). Indikasi terbanyak yang menyertai seksio sesarea adalah ketuban pecah dini (32,06%), malpresentasi (8,91%), dan oligohidramnion (8,61%). Kesimpulan dari penelitian ini adalah angka seksio sesarea di RSUD dr. Zainoel Abidin sejak berlakunya BPJS (1 Januari 2014-31 Desember 2016) mencapai 54,35%, angka ini meningkat 41,06% dari tahun 2011-2013 dengan indikasi terbanyak merupakan ketuban pecah dini (32,06%). Kata kunci: Seksio sesarea, BPJS, RS rujukan tersier  Abstract. Caesarean section is an operative procedure whereby the fetusesare delivered through an incision on the abdominal and uterine walls where normal  deliveries are not possible through maternal and neonatal indication. The incidence of caesarean section in the world is rising year after years particularly in developing countries. The rising of caesarean section rate is seen in BPJS era started since January 1st, 2014, especially in dr. Zainoel Abidin Hospital which is a tertiary referral hospital in Province Aceh.  The purpose of this study was to find out the profile of caesarean section in dr. Zainoel Abidin Hospital since the promulgation of BPJS (period January 1st, 2014- December 31st, 2016). This was a descriptive-observational study with retrospective design and total sampling technique. The data were obtained in March-April 2017. Three thousands six hundreds and fifty six secondary data from medical record were enrolled in this study. The finding showed that there were one thousand six hundreds and sixty nine vaginal deliveries (45,65%) and one thousand nine hundreds and eighty seven (54,35%) caesarean sections. The most frequent causes to caesarean sections were premature rupture of membranes (32,06%), malpresentation (8,91%), and oligohydramnion (8,61%). The conclusion of this study were the incidence of caesarean sections in dr. Zainoel Abidin Hospital since the promulgation of BPJS (January 1st, 2014-December 31st, 2016) was 54,35%, this number is increased by 41,06% than the year of 2011-2013 with the most frequent cause is premature rupture of membranes (32,06%). Keywords: Caesarean section, BPJS, Tertiary referral hospital